A cross-sectional mental-health survey of Chinese postgraduate students majoring in stomatology post COVID-19 restrictions - Zhang, Yuwei; Jia, Yue; MuLaTiHaJi, MaErWa; Mi, Yiying; Mei, Yukun; Sun, Tianxiang; Shi, Haibo; Zhang, Yifei; Zhang, Yikun; Zou, Rui; Niu, Lin; Dong, Shaojie (Frontiers in Public Health, 2024)
The psychological status of Chinese postgraduate students majoring in stomatology post the COVID-19 restrictions still remains unclear. The objective of this study was to evaluate the mental status through a cross-sectional survey and gather related theoretical evidence for psychological intervention ofon postgraduate medical students majoring in stomatology.Methods: An online survey was administered and subjectivesocial well-being, anxiety, stress and depression symptoms were assessed using the 5-item World Health Organization Well-Being Index (WHO-5), item Generalized Anxiety Disorder Scale (GAD-7), 10-item Perceived Stress Scale (PSS-10) and Patient Health Questionnaire-9 (PHQ-9), respectively. Wherein, suicidal ideation and sleep related problems were measured with PHQ-9 and Insomnia Severity Index (ISI).Results: A total of 208 participants who completed one study questionnaire were considered as valid. It was found that female respondents generally exhibited significantly higher levels of PSS-10, PHQ-9, GAD-7 scores and shorter physical activity hours than male students. Students from rural areas demonstrated significantly higher levels of PHQ-9, suicidal ideation and less portion of good/ or fair family economic support. Additionally, individuals from only only-child families reported increased levels of activity hours (1.78±2.07, p=0.045) and a higher portion (55.10%, p=0.007) of having clear future plan as compared with multiple-child families. The risk factors for anxiety symptoms (GAD-7 score) were higher scores of PSS-10 score (OR=1.15, 95%CI=1.09-1.22), PHQ-9 score (OR=1.35, 95%CI=1.22-1.49) and ISI-7 score (OR=1.14, 95%CI=1.06-1.23), while owning a clear graduation plan was the protective factor (OR=0.55, 95%CI=0.31-0.98). And the risk factors for depressive symptoms (PHQ-9) included PSS-10 (OR=1.10, 95%CI=1.04-1.16), GAD-7 (OR=1.38, 95%CI=1.25-1.52), suicidal ideation (OR=5.66, 95%CI=3.37-9.51) and ISI-7 (OR=1.17, 95%CI=1.09-1.25). Approximately 98.08% of Chinese postgraduates studying stomatology reported experiencing at least moderate stress after the COVID-19 restrictions.Within the limitations of this study, senior students were more inclined for stress, meanwhile, anxiety symptoms were related to severer levels of stress, depression, and insomnia. Depressive symptoms were associated with higher levels of stress, anxiety, insomnia, suicidal ideation and lower levels of social self-reported well-being. Thus, psychological interventions for postgraduates should be timely and appropriately implemented by strengthening social well-being, reasonably planning for the future and good physique to thereby mitigating the psychological issues after COVID-19 restrictions.